2015
DOI: 10.7717/peerj.1105
|View full text |Cite
|
Sign up to set email alerts
|

Allantoin ameliorates chemically-induced pancreaticβ-cell damage through activation of the imidazoline I3 receptors

Abstract: Objective. Allantoin is the primary active compound in yams (Dioscorea spp.). Recently, allantoin has been demonstrated to activate imidazoline 3 (I3) receptors located in pancreatic tissues. Thus, the present study aimed to investigate the role of allantoin in the effect to improve damage induced in pancreatic β-cells by streptozotocin (STZ) via the I3 receptors.Research Design and Methods. The effect of allantoin on STZ-induced apoptosis in pancreatic β-cells was examined using the ApoTox-Glo triplex assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Allantoin is a natural compound, which found in many plants, and its wound healing, anti-inflammatory, antidiabetic, and antihyperlipidemic effects have been demonstrated ( 19 20 21 22 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allantoin is a natural compound, which found in many plants, and its wound healing, anti-inflammatory, antidiabetic, and antihyperlipidemic effects have been demonstrated ( 19 20 21 22 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…showed that allantoin increased the expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), Sirt-1, and Nrf-1 in skeletal muscle cells ( 19 ). Previous studies have also indicated positive effects of allantoin on metabolic functions and streptozotocin-induced β-cells ( 20 ). We recently showed that allantoin improved NASH via downregulation of lipid metabolism-related genes such as SREBP1c, PPARα, and apolipoprotein B and attenuation of inflammation and apoptosis in methionine-choline deficient diet (MCD)-induced animals ( 21 ).…”
Section: Introductionmentioning
confidence: 94%
“…Besides, accumulated studies have revealed potential mechanisms of active compounds in YYT. The main active component of Dioscorea oppositifolia L. includes allantoin, which has been demonstrated with protective effects on pancreas β-cells in metabolic dysfunction model ( 12 ). Allantoin can also improve nonalcoholic steatohepatitis disease by activating the SIRT1/Nrf2 pathway, increasing the activities of antioxidant enzymes, and reducing lipid peroxidation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in this region are the numerous extracts, which include allantoin, dioscorin, sapogenins, prosapogenin, gracillin, choline, L-arginine, polysaccharides and proteins. Several in vitro and in vivo studies have highlighted the antidiabetic action of a number of these extracts, including dioscorea ethanol extract (18) , total saponins (19)(20)(21)(22) allantoin (23,24) , water soluble polysaccharides (25) , DA-9801 (26) and diosgenin (27,28) . However, many of these studies have been conducted in animal models in which diabetes was induced by streptozotocin (STZ) (19)(20)(21)(22) or alloxan (18,25) .…”
mentioning
confidence: 99%